A one-pot strategy for the preparation of fire-retardant poly(propylene carbonate) by terpolymerization of CO2, propylene oxide and chlorendic anhydride. (March 2023) - Wang, Wenzhen; Zhang, Xiangmin; Han, Weiwei; Huang, Jian; Zhang, Yile; Zhao, Chen; Li, Leilei
Abstract: A functional monomer chlorendic anhydride (CA) with flame retardancy was added to the polymerization reaction between CO2 and propylene oxide (PO) to form a terpolymer plastic polycarbonates (PPCCA) for the first time. Compared with conventional poly(propylene carbonate) (PPC), the synthesized PPCCA exhibited excellent thermal properties, mechanical properties, dimensional stability, high degradation and flame retardant (FR) properties. When the CA content was increased to 5 mol% (with respect to PO, except specially stated), the 5% weight-loss degradation temperatures ( T d, - 5%), the maximum weight-loss degradation temperatures ( T d, max ) and the glass transition temperature ( T g ) of PPCCA were increased to 235 ℃, 345 ℃ and 44 ℃, respectively. Additionally, in the CA content range of 0–5 mol%, the tensile strength of PPCCA increased to 26.7 ± 1.4 MPa and the elongation at break decreased to 144.4 ± 1.2%. Furthermore, within the same content range (0–5 mol%) of CA, the hot-set elongation (Δ L h ) and permanent deformation (Δ L p ) were reduced to 95% and 50%, respectively. The PPCCA exhibited good degradability as well. In terms of FR properties, the limiting oxygen index (LOI) of PPCCA (with 5 mol% CA, PPCCA5) was 33.5%, with which the vertical combustion test level turned out to be at the highest level (V-0), which truly improved the flame retardancy of the polymer. Graphical Abstract: ga1